(3GdEaUGM Yf YbO GdfcGM Ydi GdePGgH GdCQHYIs - (3MSjf Hf eMeO GdeMdj GdTGaYjs
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabHQ MSjf Hf eMeO GdeMdj GdTGaYj gPG JYdjb dWja aj GdfcGM Ydi GdePGgH GdCQHY s
(3BNQgG (B:s
(3dCfg CbQH afGH GdMGce Yfg HNdGa GdfSH dCfg djS ef Mbhb GdeGd hCf jchf fGaYkG dLejY GdCfGe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B108s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs